π0 and η meson production in proton-proton collisions at √s=8 TeV - Acharya, S.; Adam, J.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahn, S.U.; Aiola, S.; et al. (Springer New York LLC, 2018)
An invariant differential cross section measurement of inclusive π0 and η meson production at mid-rapidity in pp collisions at √s = 8 TeV was carried out by the ALICE experiment at the LHC. The spectra of π0 and η mesons were measured in transverse momentum ranges of 0.3 < p T < 35 GeV/c and 0.5 < p T < 35 GeV/c, respectively. Next-to-leading order perturbative QCD calculations using fragmentation functions DSS14 for the π0 and AESSS for the η overestimate the cross sections of both neutral mesons, although such calculations agree with the measured η/π0 ratio within uncertainties. The results were also compared with PYTHIA 8.2 predictions for which the Monash 2013 tune yields the best agreement with the measured neutral meson spectra. The measurements confirm a universal behavior of the η/π0 ratio seen for NA27, PHENIX and ALICE data for pp collisions from √s = 27.5 GeV to √s = 8 TeV within experimental uncertainties. A relation between the π0 and η production cross sections for pp collisions at √s = 8 TeV is given by m T scaling for p T > 3.5 GeV/c. However, a deviation from this empirical scaling rule is observed for transverse momenta below p T < 3.5 GeV/c in the η/π0 ratio with a significance of 6.2σ
Keywords: Physics; Particle physics; Meson; Rapidity; Nuclear physics; Large Hadron Collider; Production (economics); Order (exchange); Scaling; Quantum chromodynamics; Spectral line; https://purl.org/pe-repo/ocde/ford#1.03.04